The factors that influence the communities to participate in the co-operative / Nurul Ain Sulaiman - Sulaiman, Nurul Ain (2011)
The National Co-operative Policy (NCP) will ensure that the huge resources of the co-operatives can be harnessed to generate and contribute to the economic growth of the country. This study sought to examine the factors that influence the communities to participate in the co-operative. The objectives for this research are to study the relationships between sources of finance, facilities and advice and guidance with the participation in co-operative.Therefore, the population of study will be the members of co-operative in Pasir Mas. One hundred respondents were answer the questionnaire in other to analyze the relationship between dependent and independent variables. For the finding and analysis, the researcher use frequency distribution, descriptive statistics, hypothesis testing, and Pearson Correlation and regression analysis. For overall, the researcher can conclude that the relationship between independent and dependent variables are significant and it will lead the communities to success in the business that the communities’ involve